The Right Of Ownership In The European Law - Alikaj, Valbona (European Scientific Journal, ESJ, 2016)
The paper is about the case of the right of ownership, the social function that the constitutions of some western countries recognize to this rights and the balance of this right with other public interests. The right of ownership has a great importance even in the European judicial order. The right of ownership has undergone many changes with the creation of a single European market, so that nowadays we could not talk about only one ownership category. Special attention will be dedicated to the article 17 of the EU Charter of Fundamental Rights according to which everyone has the right to own, use, dispose of and bequeath his or her lawfully acquired possessions. The limitation of this right will be legislated toward the public interest and toward a fair compensation being paid in a good time. In its decisions, the European Court of Justice has stated that the property as a fundamental right is described not as an absolute right, for the European judge the social function has to do with the general interest that is the basis of each treaty, that is the free and full competition. The private property for the jurisprudence of the community is a fundamental right, but it could be limited due to the general economic interest that aim to be realised.